2022
DOI: 10.1071/an22025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre- and post-weaning supplementation on performance, nutritional, and metabolic characteristics in Nellore heifers under grazing

Abstract: Context Supplementation during the pre- and post-weaning periods is essential to improve the development of beef heifers in tropical pastures. Especially during the dry period, performance of heifers is limited due to low forage yield and poor nutritional value. Aim Evaluate the effect of supplementation during pre- and post-weaning periods on performance, nutritional, and metabolic characteristics in Nellore heifers under grazing. Methods Fifty-four Nellore heifers were randomly divided between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Therefore, it seems this superior immune response did not come at a metabolic cost or had no detrimental effects to other processes such as growth or, potentially, future lactations. When interpreting the lack of preserved differences in metabolic biomarkers alone, these trends are supported by Rodríguez-Sánchez et al [ 29 ] and De Paula et al [ 30 ], who also reported that metabolic differences detected in the preweaning phase were not detectable later in life. However, Kenéz et al [ 15 ] found long-term differences in the metabolic patterns of calves fed ad libitum or restricted levels of milk in the preweaning phase.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, it seems this superior immune response did not come at a metabolic cost or had no detrimental effects to other processes such as growth or, potentially, future lactations. When interpreting the lack of preserved differences in metabolic biomarkers alone, these trends are supported by Rodríguez-Sánchez et al [ 29 ] and De Paula et al [ 30 ], who also reported that metabolic differences detected in the preweaning phase were not detectable later in life. However, Kenéz et al [ 15 ] found long-term differences in the metabolic patterns of calves fed ad libitum or restricted levels of milk in the preweaning phase.…”
Section: Discussionmentioning
confidence: 69%